Identification of Perna viridis based on mitochondrial COI sequence - Amna Sulaman; Faiza Iqbal; Safia Khanum; Shahnaz Rashid; Muhammad Shafi; Faiz Muhammad (Journal of Fisheries, 2023)
The Asian green mussel (Perna viridis), a bivalve species of high economic importance, is widely distributed in the Indo-Pacific region. Here, we aimed to investigate the P. viridis species from Pakistan, a biogeographic area where nearly no P. viridis species were genetically characterized using mitochondrial cytochrome C oxidase subunit I (COI) gene to correlate it with morphologically identified species of other countries. Our results of Basic Local Alignment search Tool (BLAST) analyses show 98.7% similarity with the partial sequences of P. viridis reported from India. This study confirmed the molecular identification of P. viridis for the first time from Karachi, Pakistan and this finding is important for further taxonomic identification.